Exploring Alternative Pathways to Target Bacterial Type II Topoisomerases Using NBTI Antibacterials: Beyond Halogen-Bonding Interactions - Maja Kokot; Doroteja Novak; Irena Zdovc; Marko Anderluh; Martina Hrast; Nikola Minovski (MDPI AG, 2023)
Novel bacterial topoisomerase inhibitors (NBTIs) are a new class of antibacterial agents that target bacterial type II topoisomerases (DNA gyrase and topoisomerase IV). Our recently disclosed crystal structure of an NBTI ligand in complex with DNA gyrase and DNA revealed that the halogen atom in the para position of the phenyl right hand side (RHS) moiety is able to establish strong symmetrical bifurcated halogen bonds with the enzyme; these are responsible for the excellent enzyme inhibitory potency and antibacterial activity of these NBTIs. To further assess the possibility of any alternative interactions (e.g., hydrogen-bonding and/or hydrophobic interactions), we introduced various non-halogen groups at the p-position of the phenyl RHS moiety. Considering the hydrophobic nature of amino acid residues delineating the NBTI's binding pocket in bacterial topoisomerases, we demonstrated that designed NBTIs cannot establish any hydrogen-bonding interactions with the enzyme; hydrophobic interactions are feasible in all respects, while halogen-bonding interactions are apparently the most preferred.